Assessing The Supply Chain Risks of an Indonesian Electricity Company - Anugrah Kesuma; Ratih Dyah Kusumastuti (Quantitative Economics and Management Studies, 2024)
Energy is a crucial necessity for human societies, and access to electrical energy plays a significant role in economic development. A state-owned enterprise (SOE) is entrusted with the provision of electrical energy across Indonesia. The objective of this study is to identify and assess risk factors within the supply chain of primary distribution materials at SOE. The identification of risk factors was based on a comprehensive review of literature across various industrial sectors, further validated through consultations with senior managers at the company. For the assessment of these risks, the study employed the modified Decision Matrix Risk Assessment methodology, which involves evaluating risks based on their likelihood and impact. This evaluation was conducted through surveys distributed to 66 respondents, including planning managers, distribution managers, and commercial managers across all regional and distribution main units in Indonesia. Two risk categories with five sub-categories and a total of 27 risk factors were identified. Supply-related risks are the most significant compared to the other four sub-categories. Scarcity of raw materials, lack of capacity flexibility, and failure to make delivery requirements are in the top three rankings. This research can enrich the supply chain risk literature and provide valuable insights for utility managers in understanding supply chain risks.